(untitled) (UNED Research Journal, 2017)
Eggplant is a vegetable with innovative potential for Costa Rican market. A morphological characterization was conducted of two eggplant genotypes (JMX-292 and JMX-1099) grown under greenhouse conditions in Alajuela, Costa Rica. The qualitative variables evaluated were growth habit, leaf width, leaf spines, corolla color, fruit length, fruit calyx spines, fruit color at commercial maturity stage, and seed quantity. The quantitative variables evaluated were leaf width (cm), number of spines per leaf, fruit length (cm), number of spines per calyx, and number of seeds per fruit. There were significant differences between genotypes for number of spines per leaf (0,04 for JMX-1099 vs 1,44 for JMX-292), fruit length (15,50 vs 13,12 cm, respectively), number of spines per calyx (0,20 vs 3,48, respectively), and number of seeds per fruit (199,35 and 631,58, respectively). Both genotypes showed innovative market characteristics, like the white fruit color of JMX-292, as well as the low number of spines per leaf and per calyx and the low number of seeds per fruit of JMX-1099, so these genotypes could be interesting choices for growers.